VARIETAL RESPONSE OF BAMBARA GROUNDNUT (VIGNA SUBTERRANEA) TO MULCHING AND AMF INOCULATION IN CENTRAL NIGERIA - N.C, Odoh; Idibia, P.O.; Ncho, O.C (JOURNAL OF ADVANCES IN AGRICULTURE, 2017)
A trial was carried out in pots at the University of Abuja, Teaching and Research Farm (TRF) to evaluate the response of Bambara groundnut varieties (TVSu 460, TVSu 617, TVSU 622) to mulch and mycorrhizal inoculation. Arbuscular mycorrhizal fungal inoculum (Glomus mosseae) and leguminous mulch (Calopogonium mucunoides Desv) were respectively applied at 10 g and 100 g per pot, 2 weeks after planting. The experiment was laid out in a factorial combination in a completely randomized design with 3 replications. Plant biomass and nodulation were assessed at harvest and subjected to analysis of variance using statistical package Genstat Discovery Edition. The study revealed that combined application of mulch and G. mosseae increased the fresh root weight for all varieties ranging from 10.3 - 62.5 %. G. mosseae inoculation significantly increased the nodulation and root weight of TVSu 617 and TVSu 622 but TVSu 460 was not favored by inoculation. The enhanced shoot and root weight recorded under mulch and mycorrhizae treatments on Bambara groundnut varieties particularly could be as a result of an improved soil environment occasioned by these treatments.